Marka lokalna (regionalna) - Raszkowski, Andrzej (Local (Regional) Brand, 2006)
Local brand is directly connected with a place, region of its origin. Owing to its uniqueness and specific nature it may become an attractive product / service for outside consumers. Good local brands have positive influence on the region from which they originate and upgrade its competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 382-387